A Practical and Time-Efficient High-Intensity Interval Training Program Modifies Cardio-Metabolic Risk Factors in Adults with Risk Factors for Type II Diabetes - Phillips, Bethan E.; Kelly, Benjamin M.; Lilja, Mats; Ponce-González, Jesús Gustavo; Brogan, Robert J.; Morris, David L.; Gustafsson, Thomas; Kraus, William E.; Atherton, Philip J.; Vollaard, Niels B. J.; Rooyackers, Olav; Timmons, James A. (Frontiers in Endocrinology, 2017)
Introduction: Regular physical activity (PA) can reduce the risk of developing type 2 diabetes, but adherence to time-orientated (150 min per week or more) PA guidelines is very poor. A practical and time-efficient PA regime that was equally efficacious at controlling risk factors for cardio-metabolic disease is one solution to this problem. Herein we evaluate a new time-efficient and genuinely practical high-intensity interval training (HIT) protocol in men and women with pre-existing risk-factors for type 2 diabetes. Materials & methods: One hundred and eight-nine sedentary women (n=101) and men (n=88) with impaired glucose tolerance and/or a BMI >27 kg·m-2 (mean (range) age: 36 (18-53) y) participated in this multi-centre study. Each completed a fully supervised 6-week HIT protocol at work-loads equivalent to 100% or 125% V̇O2max. Change in V̇O2max was used to monitor protocol efficacy, while Actiheart monitors were used to determine PA during four, week-long, periods. Mean arterial (blood) pressure (MAP) and fasting insulin resistance (HOMA-IR) represent key health biomarker outcomes. Results: The higher intensity bouts ( 125% V̇O2max) used during a 5-by-1min HIT protocol resulted in a robust increase in V̇O2max (136 participants, +10.0%, p<0.001; large size-effect). 5-by-1 HIT reduced MAP ( 3%; p<0.001) and HOMA-IR ( 16%; P<0.01). Physiological responses were similar in men and women while a sizeable proportion of the training induced changes in V̇O2max, MAP and HOMA-IR was retained 3 weeks after cessation of training. The supervised HIT sessions accounted for the entire quantifiable increase in PA, and this equated to 400 MET min·week-1. Meta-analysis indicated that 5-by-1 HIT matched the efficacy and variability of a time-consuming 30-week PA program on V̇O2max, MAP and HOMA-IR. Conclusions: With a total time-commitment of <15 min per session and reliance on a practical ergometer protocol, 5-by-1 HIT offers a new solution to modulate cardio-metabolic risk factors in adults with pre-existing risk-factors for type 2 diabetes while approximately meeting the MET min·week-1 PA guidelines. Long-term randomised controlled studies will be required to quantify the ability for 5-by-1 HIT to reduce the incidence of type 2 diabetes, while strategies are required to harmonise the adaptations to exercise across individuals.